THEME: CULTURAL IMMERSION IN LANGUAGE LEARNING - Saidqulova Zuhra; Xursandova Ozoda; Safarova Dildora (Ustozlar uchun, 2025)
Cultural immersion is a powerful tool in language learning, providing authentic experiences that enhance vocabulary, pronunciation, and comprehension. By engaging with the target culture through travel, media, food, traditions, and local interactions, learners gain a deeper understanding of linguistic nuances and cultural contexts. This article explores how cultural immersion benefits language acquisition, highlights effective methods, and provides resources for learners and educators. It also recommends books and websites for further exploration. Through immersion, language learning becomes not only more effective but also more meaningful and enjoyable.